Auxological changes in survivors of childhood acute lymphoblastic leukaemia treated without cranial irradiation. (29th September 2015) - Breene, R; Williams, R; Hartle, J; Gattens, M; Acerini, C; Murray, M
Abstract : Aims: Over 80% of children with acute lymphoblastic leukaemia (ALL) achieve long-term survival, thus subsequent surveillance for late-effects of treatment is increasingly important. Increased weight gain has been reported in this group, primarily associated with cranial irradiation. No such data exists for British cohorts treated on recent protocols without cranial irradiation as standard therapy. The authors performed a retrospective study on all 134 patients enrolled on the MRC/UKALL97 protocol at a single-centre, to explore changes in height, weight and body mass index (BMI) from diagnosis of ALL. Methods: 77 patients (37M, 40F) were included; relapses, deaths or those irradiated were excluded. Median (range) age at diagnosis 4.6 (1.1–15.9) years. Height-, weight- and BMI- SD-scores (SDS) generated from age- and population-referenced normative data were recorded at diagnosis and annually until 3 years-out (YO) from end-of-treatment (EoT). Changes with time from diagnosis in whole-group and gender subgroups and between-group comparison (for gender, diagnostic white cell count and steroid administered) were explored using a univariate model (post hoc analysis with Dunnett's two-sided test for multiple comparisons; p value ≤0.001 significant). Results: *p<0.0001. Whole- and gender subgroup data are summarised in table 1 . Whole-group height-SDS* were lower from 1 year into treatment until 2YO. Weight-* and BMI-SDS* remained higher 3YO. In females, height-SDS* was lower until EoT, but higher weight-* and BMI-SDS* persisted 3YO. In males, height-SDS* was lower from EoT until 2YO, while higher weight-SDS* persisted 3YO. However, effects on BMI-SDS had resolved by 2YO. Between-group change in height-, weight- and BMI-SDS from diagnosis to 3YO were not different by gender, diagnostic white-cell-count or steroid administered (data not shown). Conclusions: Survivors of childhood ALL exhibit adverse changes in height-, weight- and BMI-SDS which arise during treatment and persist into follow-up. In males, effects on BMI are transient and likely reflect effects of both disease and therapy on linear growth. In females, despite recovery of height, BMI remains increased secondary to weight gain. Potential mechanisms include increased appetite through steroid-induced hypothalamic-pituitary-axis re-programming and/or reduced exercise. Strategies, such as dietary and lifestyle modification advice, should be implemented in order to minimise associated long-term morbidity.